Circ-MKLN1/miR-377-3p/CTGF Axis Regulates the TGF-β2-induced Posterior Capsular Opacification in SRA01/04 Cells. (4th March 2022) - Liu, Jiajia; Dong, Yiran; Ji, Qingshan; Wen, Yuechun; Ke, Genjie; Shi, Lei; Guan, Wei; Xu, Weiping
ABSTRACT: Objective: Posterior capsular opacification (PCO) is a common postoperative ocular complication after cataract surgery. Little research focused on the regulation of circular RNAs (circRNAs) in PCO. This study was designed to investigate the function of circRNA-muskelin (circ-MKLN1) in PCO. Methods: SRA01/04 cells were treated with transforming growth factor (TGF)-β2. Cell viability was analyzed by Cell Counting Kit-8 (CCK-8) assay. Transwell assay was used for cell migration and invasion detection. Cell migration was also measured by wound healing assay. Epithelial-mesenchymal transition (EMT)-related proteins and connective tissue growth factor (CTGF) were quantified using western blot. Results: Cell viability, migration, invasion and EMT process in SRA01/04 cells were facilitated by TGF-β2. Circ-MKLN1 expression was enhanced in 17 PCO lens samples relative to 19 normal lens samples and TGF-β2-treated SRA01/04 cells contrasted to control cells. Downregulation of circ-MKLN1 inhibited the effects of TGF-β2 on SRA01/04 cells. Circ-MKLN1 targeted miR-377-3p and the regulation of si-circ-MKLN1 for the TGF-β2-induced influences was related to the upregulation of miR-377-3p. CTGF was the target gene for miR-377-3p. CTGF knockdown also abolished the TGF-β2-mediated cell growth, migration and invasion of SRA01/04 cells. The function of miR-377-3p was achieved by reducing the CTGF level. TGF-β2-induced CTGF expression promotion was alleviated by si-circ-MKLN1 through upregulating the expression of miR-377-3p. Conclusion: These results showed that circ-MKLN1 contributed to the progression of PCO in vitro by increasing the CTGF expression via sponging miR-377-3p. Circ-MKLN1 might be important for improving the molecular target therapy in PCO.